Subjective religiosity as resilience to stressful life events in middle-aged and older African Americans - Brown, Shari A. (Journal of religion, spirituality & aging, 2023)
This study examined stressful life events, discrimination, and well-being among older African Americans. Through a risk and resilience framework we evaluate the role of subjective religiosity as a moderator. Stressful life events and discrimination represent a double jeopardy risk profile in which discrimination exacerbates the negative relationship between stressful life events and well-being. Subjective religiosity is a resilience resource that should buffer the effect of discrimination on the stress – well-being link. Stressful life events and discrimination predicted poorer well-being, discrimination exacerbated the negative effects of stressful life events on depression and life-satisfaction, but subjective religiosity reduced these effects.